2005
DOI: 10.1002/dvdy.20623
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of early Xenopus development by ErbB signaling

Abstract: ErbB signaling has long been implicated in cancer formation and progression and is shown to regulate cell division, migration, and death during tumorigenesis. The functions of the ErbB pathway during early vertebrate embryogenesis, however, are not well understood. Here we report characterization of ErbB activities during early frog development. Gain-of-function analyses show that EGFR, ErbB2, and ErbB4 induce ectopic tumor-like cell mass that contains increased numbers of mitotic cells. Both the muscle and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…Neuregulins signal through the EGF receptor ErbB tyrosine kinase, and this signaling pathway has been shown to contribute to convergent and extension movements during gastrulation. However, a knock-down of ErbB3 or ErbB4 did not inhibit Brachyury expression in the notochord, suggesting that ADAM19 function may act through a different pathway (Nie and Chang, 2006, 2007a,b). On the other hand, we found that ADAM19 knock-down decrease pAKT a known target of the EGF signaling pathway.…”
Section: Discussionmentioning
confidence: 98%
“…Neuregulins signal through the EGF receptor ErbB tyrosine kinase, and this signaling pathway has been shown to contribute to convergent and extension movements during gastrulation. However, a knock-down of ErbB3 or ErbB4 did not inhibit Brachyury expression in the notochord, suggesting that ADAM19 function may act through a different pathway (Nie and Chang, 2006, 2007a,b). On the other hand, we found that ADAM19 knock-down decrease pAKT a known target of the EGF signaling pathway.…”
Section: Discussionmentioning
confidence: 98%
“…Overexpression in Frog Embryos-Embryos were obtained and maintained as described previously (27). All experiments involving X. laevis were approved by University of Alabama at Birmingham Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…The distribution of activated PI3K signaling components during early Xenopus development has not been described. ErbB receptors, as well as the neuregulin 1 (NRG1) ligand, are expressed maternally and throughout early frog embryogenesis (Yang et al, 1998(Yang et al, , 1999Nie and Chang, 2006). Since inhibition of ErbB signaling does not block mesoderm formation and patterning but interferes with gastrulation Chang, 2006, 2007), we propose that ErbB signaling mainly regulates the second phase of PI3K and MAPK activation during gastrulation, but is dispensable for PI3K-and MAPKdependent mesodermal induction.…”
Section: Pi3k and Mapk In Mesoderm Induction And Gastrulationmentioning
confidence: 96%